2007
DOI: 10.3892/or.17.2.417
|View full text |Cite
|
Sign up to set email alerts
|

Induction of α2-antiplasmin inhibits E-cadherin processing mediated by the plasminogen activator/plasmin system, leading to suppression of progression of oral squamous cell carcinoma via upregulation of cell-cell adhesion

Abstract: The plasminogen activator/plasmin system is one of the main protease systems involved in tumor cell invasion and metastasis. Our previous study has shown that plasmin degrades E-cadherin and promotes cell dissemination by downregulation of E-cadherin-mediated cell-cell adhesion in oral squamous cell carcinoma (SCC) cells. To examine the effect of downregulation of the plasminogen activator/plasmin system by •2-antiplasmin (•2-AP) on cell-cell adhesion mediated by E-cadherin in oral SCC cells, the oral SCC cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Although our study is consistent with the wellknown link between the activation of VEGF-D and both the remodelling of tumour lymphatics and lymph node metastasis (Harris et al, 2011(Harris et al, , 2013, the diversity of effects of the uPA/plasmin axis means we cannot completely exclude the possibility that the effects of plasmin in our model were in part due to mechanisms not involving the proteolytic processing of VEGF-D. For example, it was previously shown that driving expression of a 2 -AP in oral squamous cell carcinoma cells led to inhibition of proteolysis of E-cadherin resulting in reduced cell motility and suppression of tumourigenicity in mice (Hayashido et al, 2007). In the tumour model, we employed here, it is possible that plasmin enhanced the motility of tumour cells, thereby facilitating their access and entry to intra-tumoural lymphatics induced by VEGF-D.…”
Section: Discussionmentioning
confidence: 93%
“…Although our study is consistent with the wellknown link between the activation of VEGF-D and both the remodelling of tumour lymphatics and lymph node metastasis (Harris et al, 2011(Harris et al, , 2013, the diversity of effects of the uPA/plasmin axis means we cannot completely exclude the possibility that the effects of plasmin in our model were in part due to mechanisms not involving the proteolytic processing of VEGF-D. For example, it was previously shown that driving expression of a 2 -AP in oral squamous cell carcinoma cells led to inhibition of proteolysis of E-cadherin resulting in reduced cell motility and suppression of tumourigenicity in mice (Hayashido et al, 2007). In the tumour model, we employed here, it is possible that plasmin enhanced the motility of tumour cells, thereby facilitating their access and entry to intra-tumoural lymphatics induced by VEGF-D.…”
Section: Discussionmentioning
confidence: 93%
“…Alpha-2-antiplasmin constitutes a key recognition sequence for cell adhesions (Thomas et al, 2007), and has been reported to enhance cell aggregation and suppress cell mobility (Hayashido et al, 2007). It has also been found to be involved in mammalian spermatogenesis, sperm capacitation, and fertilization, as reviewed by Liu (2007).…”
Section: Biomarker Candidatesmentioning
confidence: 98%
“…Another interaction partner was pigment epitheliumderived factor (PEDF), which is the major circulating inhibitor of plasmin. With this interaction, PEDF is linked to the plasminogen activator/plasmin system, which is one of the main protease systems involved in tumour cell invasion and metastasis (Hayashido et al, 2007). Only recently PEDF was also identified as a key inhibitor of stromal vasculature in the mural pancreas.…”
Section: Klk6-expression Was High In Nearly All Measured Cell Lines (B)mentioning
confidence: 99%